The Effect of Borax Solution as Preservative to The Mechanical Properties of Bamboo - M.A.P Handana; Surbakti, Besman; Karolina, Rahmi (International Journal of Sustainable Construction Engineering and Technology, 2020)
The use of borax solution as a preservative in wood and bamboo materials is well known in the community. A borax solution is an environmentally friendly liquid that can dissolve in water, so it is suitable to be used as a preservative within cold or hot soaking techniques. The ability of borax to resist insects and fungus attacks on bamboo has been proven, but the effect of the solution on the strength of bamboo must also be investigated. This study conducts to investigate the effects of borax and its additives as preservative solutions to the mechanical properties of bamboos. The bamboos preservations were conducted by cold conditions of immersion, while the mechanical properties were performed to understand the effects of preservatives. The result of this study indicated that 30% to 50% borax in the preservative solution is sufficient to provide significant increase in strength for compressive strength, tensile strength, and bending strength of bamboo specimen. From this study, the use of borax solution in preserving the bamboos materials improved the quality of bamboos based on its mechanical properties.